Nasal Tip-Suspending Suture Technique: Cat's Nape Suture - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Variation in nasal-tip deformity is the most common complaint of the patients requesting rhinoplastic surgery, and the goal of nearly every rhinoplasty is to achieve ideal nasal-tip rotation and projection. We describe a procedure that allows the surgeon to secure nasal-tip rotation and projection through a suspension suture technique. Preserving the interalar soft tissues over the dorsal caudal septum and interdomal ligaments during the surgery is the major basis of this technique. We use the soft tissues as a suspending material for the tip complex, which acts like one whole part.
Keywords: Nasal tip sutures; nasal tip shape; PROJECTION; ROTATION